Load testing and GPR assessment for concrete bridges on military installations - Varela-Ortiz, Wilmel; Cintrón, Carmen Y. Lugo; Velázquez, Gerardo I.; Stanton, Terry R. (Construction & building materials, 2013)
► Four concrete bridges were load tested and modeled (FEM). ► FEM were subject to civilian and military moving loads. ► Live load distribution factors were obtained for moving loads from FEM. ► Load test and GPR are useful to determine safe load carrying capacities of bridges. The US Army owns and maintains approximately 2000 bridges on its installations spread out in the United States and around the world. From this inventory, 67% are concrete bridges, most of which do not have design or as-built plans to effectively evaluate their condition/capacity. In addition, military vehicles have unique characteristics that are difficult to take into account when analytical analyses are performed. For these purposes, the US Army Engineer Research and Development Center has been adapting non-destructive techniques. The most promising concept explored thus far involves bridge rating through non-destructive load testing in combination with Ground Penetrating Radar (GPR) techniques. Field load testing techniques are valuable for evaluating the capacity of existing bridges and accurately characterize the structure’s live-load response while GPR techniques provide valuable information regarding the internal reinforcement as well as the condition of the concrete. This article will provide a brief description as well as the results from recent evaluations performed on reinforced concrete bridges at military installations.